ACT-i, an insomnia intervention for autistic adults: a pilot study. Issue 2 (20th March 2023) - Lawson, Lauren P.; Richdale, Amanda L.; Denney, Kathleen; Morris, Eric M.J.
Abstract: Background: Insomnia and disturbed sleep are more common in autistic adults compared with non-autistic adults, contributing to significant social, psychological and health burdens. However, sleep intervention research for autistic adults is lacking. Aims: The aim of the study was to implement an acceptance and commitment therapy group insomnia intervention (ACT-i) tailored for autistic adults to examine its impact on insomnia and co-occurring mental health symptoms. Method: Eight individuals (6 male, 2 female) aged between 18 and 70 years, with a clinical diagnosis of autism spectrum disorder, and scores ranging from 9 to 26 on the Insomnia Severity Index (ISI) participated in the trial. Participants were assigned to one of two intervention groups (4 per group) within a multiple baseline over time design for group. Participants completed questionnaires pre-intervention, post-intervention, and at 2-month follow-up, actigraphy 1 week prior to intervention and 1 week post-intervention, and a daily sleep diary from baseline to 1 week post-intervention, and 1 week at follow-up. Results: At a group level there were significant improvements in ISI (λ 2 =10.17, p =.006) and HADS-A (anxiety) (λ 2 =8.40, p =.015) scores across the three time points. Clinically reliable improvement occurred for ISI scores ( n= 5) and HADS-A scores ( n= 4) following intervention. Client satisfaction indicated that ACT-i was an acceptable intervention to the participants (median 4 out of 5). Conclusions: This pilot study with eight autistic adults indicates that ACT-i is both an efficacious and acceptable intervention for reducing self-reported insomnia and anxiety symptoms in autistic adults.